Translation bibliomigrancy: the case of contemporary French Caribbean literature in Sweden - Lindqvist, Yvonne (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
This paper examines consecration mechanisms contributing to translation taking place from one local periphery in the global translation field, notably from French Caribbean literature, to another (semi-) periphery, Swedish literature. The translation bibliomigrancy of Dany Laferrière, Maryse Condé and Patrick Chamoiseau is mapped out and tested against the Double Consecration Hypothesis, which states that writers from peripheral cultures, to be selected for translation into Swedish, have primarily to be consecrated within the center of their previous (colonial) culture in the global translation field and then within the centers of the British and American literary cultures. It is shown that double consecration constitutes a favorable condition for the peripheral writers studied to reach Swedish readers in translation. However, the success of these writers within Swedish literary culture heavily depends on their consecration within the Anglo-American culture, on the prestige of the publishing houses and on the involved translators’ possession of translation capital.